2010
DOI: 10.3109/00365513.2010.504281
|View full text |Cite
|
Sign up to set email alerts
|

Apelin: A potential link between inflammation and cardiovascular disease in end stage renal disease patients

Abstract: Apelin is related to echocardiographic features and inflammatory markers in hemodialyzed patients. Apelin may provide a mechanism for systemic inflammatory monitoring and adaptive regulation of cardiovascular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…Contrary to us, earliest studies reported lower apelin values in dialysis patients compared to healthy individuals and the decrease was more in those with more severe heart impairment. 18,26 However, Codognotto et al found lower apelin levels in HD patients with cardiomyopathy than in non-uremic precedents and concluded that uremia, not the severity of heart failure, was the determinant for apelin reduction. 27 On the other hand, in support to our results, three recent papers did not show a difference between apelin in dialysis patients and healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to us, earliest studies reported lower apelin values in dialysis patients compared to healthy individuals and the decrease was more in those with more severe heart impairment. 18,26 However, Codognotto et al found lower apelin levels in HD patients with cardiomyopathy than in non-uremic precedents and concluded that uremia, not the severity of heart failure, was the determinant for apelin reduction. 27 On the other hand, in support to our results, three recent papers did not show a difference between apelin in dialysis patients and healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Recently clinical and experimental studies indicated a link between apelin and inflammation. [15][16][17][18] Plasma apelin has been shown to negatively correlate with inflammatory markers in hemodialyzed patients. 18 Based upon the evidence of malnutrition and inflammation and considering the putative role of adipose tissue in CKD, we aimed to evaluate whether serum apelin could reflect the nutritional status of children on peritoneal dialysis (PD) and hemodialysis (HD).…”
Section: Introductionmentioning
confidence: 99%
“…6 We found that serum level of apelin is lower in the nondiabetic group who had undergone a shorter length of hemodialysis pretransplant, our results agree with those reported by El-Shehaby and associates, who, in 2010, studied the plasma level of apelin in patients with hemodialysis to assess the effect of renal transplant and dialysis session on plasma apelin and found that plasma apelin levels were significantly lower in hemodialysis patients compared with controls while levels increased significantly in the early posttransplant period. 12 Leal and associates found no difference between apelin-36 levels in hemodialysis patients and healthy subjects. In contrast apelin-12 levels were significantly higher in patients compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…15,30 Studies have shown that apelin levels increase in mildly symptomatic heart failure but decrease in more symptomatic patients without statistically significant difference between functional classes or correlation with EF. 31,32 El-Shehaby et al 23 reported that apelin is positively correlated with echocardiographic measurements and negatively correlated with hsCRP and IL-6 levels in HD patients showing its role in systemic inflammatory response and cardiovascular functions. With all these data from the literature, it may be speculated that hypervolemia and the resulting hypertension provokes increased levels of apelin to provide diuresis, vasodilation, and increased cardiac contractility.…”
Section: Discussionmentioning
confidence: 99%
“…16 Apelin is thought to have actions effective on cardiovascular and renal functions and fluid status like stimulation of nitric oxide (NO) related vasodilation; 17 vasoconstriction in the presence of dysfunctional endothelium, 18 positive inotropic effects; 19 inhibition of antidiuretic hormone (ADH) release, 20 and antagonistic effects to renin-angiotensin-system (RAS). 21 Apelinergic system has also been reported to have roles in the pathogenesis of coronary disease secondary to chronic renal failure, 22 systemic inflammatory response, and cardiovascular functions 23 and renal physiology like vasodilatation of afferent and efferent arterioles; inhibition of angiotensin-2 (AT2) induced increase in intracellular calcium (Ca) via NO release. 24 In our study, we primarily aimed to investigate the hydration status of PD patients by BIS and echocardiography.…”
Section: Introductionmentioning
confidence: 99%